Pollination Efficiency of Managed Bee Species (Apis mellifera and Bombus pauloensis) in Highbush Blueberry (Vaccinium corymbosum) Productivity - Cavigliasso, Pablo (2020)
Understanding how bees use the resources provided by crops of massive flowering is essential to develop meaningful agricultural management of plans to maximize the potential of pollination service. We assessed the effect of the pollination carried out by native species Bombus pauloensis and Apis mellifera on the production and quality of blueberry fruits. In this context, we tested the prediction that pollinator assemblages benefit fruit yield. Four treatments were performed: open pollination, B. pauloensis pollination, A. mellifera pollination, and autogamy. For each treatment, the frequency of floral visitors, fruit setting, yield, and quality were evaluated. The results showed that Vaccinium corymbosum L. ‘Emerald’ is highly dependent on entomophilous pollination to obtain optimal production and high-quality fruit, and that pollination with A. mellifera generated the highest proportion of fruit setting (0.80 ± 0.03). The highest seed number was found in open pollinated fruits. This study highlights the effect of the interactions among wild and managed pollinators on the productivity of commercial blueberry fields, and is the first report of B. pauloensis use in blueberry pollination.